Evaluating the Effectiveness of Reading and Arithmetic Initiative for Teachers of the First Three Grades in Mafraq Governorate from their Point of View - Al Saoud, Ibtisam Mohammad Suleiman (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the degree of evaluation of the effectiveness of the reading and arithmetic initiative among teachers of the first three grades in Mafraq Governorate from their point of view. The study sample consisted of (110) male and female teachers from public schools in Mafraq Governorate. The study used the descriptive survey method, and the results showed a medium evaluation degree. The effectiveness of the reading and arithmetic initiative among teachers of the first three grades in Mafraq Governorate from their point of view with mean (3.42), the domain of the content of the class came in the first place with a mean of (3.68), a standard deviation (0.69) and a high degree, while the activities and strategies domain came in the second place with mean of (3.36), a standard deviation (0.71) and a medium degree. The evaluation domain came with an mean (3.23) and a medium degree. It also showed that there were no statistically significant differences attributed to the variable of teaching experience in all areas and the tool as a whole. In light of this, the study presented a set of recommendations, most notably conducting intensive training courses for teachers. The first three grades focus on the skills of the reading and arithmetic initiative, and provide a professional and school climate that enhances those skills.